Determination of domperidone in human plasma by LC-MS and its pharmacokinetics in healthy Chinese volunteers. - WU Min-Shu; GAO Ling; CAI Xiao-Hui; WANG Guang-Ji (Acta Pharmacologica Sinica, 2016)
AIM: To determine the concentration of domperidone in human plasma and investigate its pharmacokinetics in Chinese male volunteers following oral administration of a single dose of the medicine 20 mg. METHODS: Plasma samples were processed by liquid-liquid extraction and a liquid chromatographic-mass spectrometric assay was developed for the determination of domperidone in human plasma. RESULTS: Assay linearity was obtained in the range of 0.52 - 154.5 microg/L (r = 0.9999). The recovery of domperidone from human plasma was more than 75 %. The intraday and interday relative standard deviations (RSD) for the lowest concentration examined (0.52 microg/L) were 9.4 % and 7.6 %, respectively. The method was utilized to determine the concentration of domperidone in Chinese male volunteers. The concentration-time curve was fitted to a two-compartment model. Its main pharmacokinetic parameters were: Tmax = (0.8 +/- 0.7) h, Cmax = (50 +/- 32) microg/L, T1/2 = (7.8 +/- 1.6) h. CONCLUSION: The method described in this report was of high sensitivity and selectivity for accurate determination of the plasma concentration of domperidone in human.